Model of development of professional culture of teachers of special subjects building profile - Mikhnyuk, Maria (Professional Pedagogics, 2014)
This article describes the content model of the development of the professional culture of teachers of special disciplines of the construction profile. It is proved that the model must contain components that directly affect the effectiveness of this development. The structure of the model constitute a promising target, theoretical and methodological, conceptual and technological, procedural activity and reflective evaluation blocks. Promising target block defines the strategy implementation of the model. Theoretical and methodological block examines the theoretical principles and theory development, methodological framework and research approaches. Meaningful technology unit provides for the development of the professional culture of teachers of special disciplines, technology development, formation of a teacher with predetermined quality professional performance. Procedural activity unit provides for the development of professional culture in the system of methodical work professional technical educational institution (PTEI), including through the participation of the teachers of special disciplines in various collective and mass methodical activities in the School development professional culture, as well as in the process of self-educational activity. Reflective-evaluative unit is aimed at diagnosing the development of a professional culture at all stages of development due to the proposed criteria, indicators and levels.